The mediating role of loneliness in the relationship between parent-child conflict and academic buoyancy - Houshang Garavand (University of Hormozgan, 2022)
The purpose of this study was to investigate the mediating role of loneliness in the relationship between parent-child conflict with academic buoyancy. The research method was correlation of the type structural equation modeling. The population of this study included all undergraduate students of Lorestan University in the academic year 2021-2022.The statistical sample size was determined based on Klein's thumb rule equal to 240 people which was done by accessible sampling method and online questionnaire. The instruments used in this study were UCLA LONELINESS SCALE, Parent Child Relationship Scale (PCRS) and Dehghanizadeh and Husseinchari academic buoyancy questionnaires. Data analysis was performed using structural equation modeling. Statistical analysis was done by the SPSS-22 and AMOS-24 software. The results showed that parent-child conflict had no direct and causal effect on academic buoyancy. The results about the indirect relationships in the model showed that the parent-child conflict is mediated by the feeling of loneliness on academic vitality. Therefore, it is suggested that the necessity of establishing good and friendly relations between parents and young people should be raised in universities, parents should be aware of the consequences of their children's loneliness and provide their children with emotional, material and informational support.